Assessing participation of children with acquired brain injury and cerebral palsy: a systematic review of measurement properties. (23rd January 2020) - Resch, Christine; Van Kruijsbergen, Mette; Ketelaar, Marjolijn; Hurks, Petra; Adair, Brooke; Imms, Christine; De Kloet, Arend; Piskur, Barbara; Van Heugten, Caroline
Abstract : Aim: To examine which instruments used to assess participation of children with acquired brain injury (ABI) or cerebral palsy (CP) align with attendance and/or involvement constructs of participation; and to systematically review measurement properties of these instruments in children with ABI or CP, to guide instrument selection. Method: Five databases were searched. Instruments that quantified 'attendance' and/or 'involvement' aspects of participation according to the family of participation‐related constructs were selected. Data on measurement properties were extracted and methodological quality of the studies assessed. Results: Thirty‐seven instruments were used to assess participation in children with ABI or CP. Of those, 12 measured attendance and/or involvement. The reliability, validity, and responsiveness of eight of these instruments were examined in 14 studies with children with ABI or CP. Sufficient measurement properties were reported for most of the measures, but no instrument had been assessed on all relevant properties. Moreover, most psychometric studies have marked methodological limitations. Interpretation: Instruments to assess participation of children with ABI or CP should be selected carefully, as many available measures do not align with attendance and/or involvement. Evidence for measurement properties is limited, mainly caused by low methodological study quality. Future studies should follow recommended methodological guidelines. What this paper adds: Twelve instruments used to assess participation of children with acquired brain injury (ABI) or cerebral palsy (CP) aligned with attendance/involvement. Seven instruments have some psychometric evidence supporting their use with children with CP. For children with ABI, only the Child and Adolescent Scale of Participation has shown preliminary evidence of measurement properties. What this paper adds: Twelve instruments used to assess participation of children with acquired brain injury (ABI) or cerebral palsy (CP) aligned with attendance/involvement. Seven instruments have some psychometric evidence supporting their use with children with CP. For children with ABI, only the Child and Adolescent Scale of Participation has shown preliminary evidence of measurement properties. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Resumen: Evaluación de la participación de niños con lesión cerebral adquirida y parálisis cerebral: una revisión sistemática de las propiedades de escalas de medición Objetivo: Examinar qué instrumentos utilizados para evaluar la participación de niños con lesión cerebral adquirida (ABI) o parálisis cerebral (PC) se alinean con los constructos de participación de concurrencia y / o participación directa (involucramiento); y para revisar sistemáticamente las propiedades de medición de estos instrumentos en niños con ABI o CP, para guiar la selección de instrumentos. Método: Se realizaron búsquedas en cinco bases de datos. Se seleccionaron los instrumentos que cuantificaron los aspectos de 'concurrencia' y / o 'participación directa' según la familia de construcciones relacionadas con la participación. Se extrajeron los datos sobre las propiedades de medición y se evaluó la calidad metodológica de los estudios. Resultados: Se utilizaron 37 instrumentos para evaluar la participación en niños con ABI o PC. De ellos, 12 midieron concurrencia y / o participación directa. La fiabilidad, validez y capacidad de respuesta de ocho de estos instrumentos se examinaron en 14 estudios con niños con ABI o PC. Se informaron propiedades de medición suficientes para la mayoría de los dominios, pero no se evaluó ningún instrumento en todas las propiedades relevantes. Además, la mayoría de los estudios psicométricos tienen marcadas limitaciones metodológicas. Interpretación: Los instrumentos para evaluar la participación de niños con ABI o PC deben seleccionarse cuidadosamente, ya que muchas medidas disponibles no se alinean con la concurrencia y / o participación directa (involucramiento). La evidencia de las propiedades de medición es limitada, causada principalmente por la baja calidad del estudio metodológico. Los estudios futuros deben seguir las pautas metodológicas recomendadas. Resumo: Avaliando participação de crianças com lesão cerebral adquirida e paralisia cerebral: uma revisão sistemática de propriedades de medida Objetivo: Examinar quais instrumentos usados para avaliar participação de crianças com lesão cerebral adquirida (LCA) ou paralisia cerebral (PC) se alinham com os constructos de comparecimento e/ou envolvimento da participação; e revisar sistematicamente as propriedades de medida destes instrumentos em crianças com LCA ou PC, para guiar a seleção de instrumentos. Método: Cinco bases de dados foram pesquisadas. Os instrumentos que quantificaram aspectos da participação de "comparecimento" e/ou "envolvimento" segundo a família de construtos relacionados à participação foram selecionados. Os dados das propriedades de medida foram extraídos, e a qualidade metodológica dos estudos foi avaliada. Resultados: Trinta e sete instrumentos foram usados para avaliar a participação em crianças com LCA ou PC. Destas, 12 mediram comparecimento e/ou envolvimento. A confiabilidade, validade, e responsividade de oito destes instrumentos foram examinados em 14 estudos com crianças com ABI ou PC. Propriedades de medidas suficientes foram reportadas para a maioria das medidas, mas nenhum instrumento teve todas as propriedades relevantes avaliadas. A maioria dos estudos psicométricos teve limitações metodológicas importantes. Interpretação: Instrumentos para avaliar a participação de crianças com LCA ou PC devem ser selecionados cuidadosamente, já que muitas medidas disponíveis não se alinham com o comparecimento/envolvimento. Evidências das propriedades de medida são limitadas, principalmente devido à baixa qualidade metodológica dos estudos. Futuros estudos devem seguir diretrizes metodológicas recomendadas.